Journal of Environmental Planning and Management - Journal of Environmental Planning and Management (Taylor & Francis, 2026)
Journal of Environmental Planning and Management (JEPM) is a leading international forum for scholarly and accessible papers on all aspects of environmental planning and management. The aim of journal of Environmental Planning and Management is to focus on the practical, technical, social and political problems in the planning and management of the environment. Journal of Environmental Planning and Management accepts articles that encompass applied research, the application of new approaches and techniques, the evaluation of policy and practice, critical 'state-of-the-art' reviews papers, and contributions from integrated and cross-disciplinary research teams, policy makers and practitioners.
FI 0.9
Q1
Keywords: Geography; Planning; Urban & Environment; Acuerdos transformativos; Transformative agreements; Gestión ambiental; Desarrollo sostenible; Política ambiental; Recursos naturales; Evaluación de impacto ambiental